Introducing a day-case arthroplasty pathway significantly reduces overall length of stay. (1st November 2021) - Saunders, Paul; Smith, Nick; Syed, Farhan; Selvaraj, Thomas; Waite, Jon; Young, Stephen
Abstract : Aims: Day-case arthroplasty is gaining popularity in Europe. We report outcomes from the first 12 months following implementation of a day-case pathway for unicompartmental knee arthroplasty (UKA) and total hip arthroplasty (THA) in an NHS hospital. Methods: A total of 47 total hip arthroplasty (THA) and 24 unicompartmental knee arthroplasty (UKA) patients were selected for the day-case arthroplasty pathway, based on preoperative fitness and agreement to participate. Data were likewise collected for a matched control group (n = 58) who followed the standard pathway three months prior to the implementation of the day-case pathway. We report same-day discharge (SDD) success, reasons for delayed discharge, and patient-reported outcomes. Overall length of stay (LOS) for all lower limb arthroplasty was recorded to determine the wider impact of implementing a day-case pathway. Results: Patients on the day-case pathway achieved SDD in 47% (22/47) of THAs and 67% (16/24) of UKAs. The most common reasons for failed SDD were nausea, hypotension, and pain, which were strongly associated with the use of fentanyl in the spinal anaesthetic. Complications and patient-reported outcomes were not significantly different between groups. Following the introduction of the day-case pathway, the mean LOS reduced significantly by 0.7, 0.6, and 0.5 days respectively in THA, UKA, and total knee arthroplasty cases (p < 0.001). Conclusion: Day-case pathways are feasible in an NHS set-up with only small changes required. We do not recommend fentanyl in the spinal anaesthetic for day-case patients. An important benefit seen in our unit is the so-called 'day-case effect', with a significant reduction in mean LOS seen across all lower limb arthroplasty. Cite this article: Bone Jt Open  2021;2(11):900–908.